The teaching cultural capital in the educational inclusion processes - Ortiz Huerta, Manuel Gregorio; Zacarías Gutiérrez, Mauricio (IE Revista de Investigación Educativa de la REDIECH, 2021)
This essay raises the cultural capital issue that teachers face as a detriment of inclusive practices in school when pedagogical elements such as pedagogy, school and schooling do not consider student diversity. Cultural practices, the meaning and significance of school and the mandatory of education in the neoliberal system are mechanisms that are incompatible with the processes of inclusion of the student in school; the cultural capital of the teacher founds a conservative pedagogy that is linear to the curriculum and the neoliberal political-pedagogical system because it is effective for the interests of said system. The cultural capital of teachers created by conservative cultural practices forms a habitus in the student that inhibits their presence, participation and belonging; therefore, reflection on educational practice is required from a pedagogy of differences that gives meaning and significance to the experiences of the other and socially constructs otherness.